The Influence of Literacy Culture on the Pedagogical Competence of Buddhism Teachers at SMA/SMK Level in Indonesia - Agus Subandi; Urip Widodo; Widia Darma; Santi Paramita (Jurnal Pendidikan Edutama, 2024)
Teachers who still do not have pedagogical competence are not able to create good learning conditions and cannot condition students' learning methods to be effective and successful due to teachers' literacy culture and limited ability to manage learning. The aim of this research was to determine the influence of literacy culture on the pedagogical competence of high school/vocational school level Buddhist teachers in Indonesia. This research uses quantitative research methods. This researcher used a survey approach with a sample of 37 high school/vocational school teachers in various regions in Indonesia via Google form. The results of this research are that literacy culture influences teacher pedagogical competence. This is proven by the regression coefficient value of the literacy culture variable (t calculated) which is 2.835 compared to the t table of 2.059, the significance of the literacy culture variable on the related variable, namely teacher pedagogical competence, is 0.009 or smaller than the error threshold value of 0.05.